Supervisory Function on Judges: Prevent Corruption Context - Edy Hasmi (The Southeast Asia Law Journal, 2016)
The purpose of this research was to determined the effectiveness of the supervision of the Supreme Court judges in Indonesia. Supervision the code of ethics and code of conduct of judges can be seen from the number of public complaints on judges are immoral and detention of judges by the Corruption Eradication Commission. The method used in this research was normative legal research/normative juridical, the data were analyzed descriptively qualitative. The research founded that The Supreme Court’s role in the framework of the supervision of judges has not been effective. This research suggested that judges should have high integrity, visionary, and also understanding for law and social sciences, and also should have the intellectual character, thus judges feel protected by the presence of the Supreme Court.